2008
DOI: 10.1016/j.ab.2007.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Screening of potential a disintegrin and metalloproteinase with thrombospondin motifs-4 inhibitors using a collagen model fluorescence resonance energy transfer substrate

Abstract: The major components of the cartilage extracellular matrix are type II collagen and aggrecan. Type II collagen provides cartilage with its tensile strength, whereas the water-binding capacity of aggrecan provides compressibility and elasticity. Aggrecan breakdown leads to an increase in proteolytic susceptibility of articular collagen; hence, aggrecan may also have a protective effect on type II collagen. Given their role in aggrecan degradation and differing substrate specificity profiles, the pursuit of inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…1F ). Thus, adding piceatannol (PIC), a selective inhibitor of ADAMTS-4 and -5 [41] , to the cell cultures induced a strong inhibition of Reelin cleavage at both, the N- and C-terminal site ( Fig. 2A and Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1F ). Thus, adding piceatannol (PIC), a selective inhibitor of ADAMTS-4 and -5 [41] , to the cell cultures induced a strong inhibition of Reelin cleavage at both, the N- and C-terminal site ( Fig. 2A and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since it was shown that ADAMTS-4 and ADAMTS-5 (aggrecanase-2) have a number of common substrates and overlapping physiological roles [46] , and that both ADAMTS-4 and -5 are inhibited by α2M and piceatannol [41] , [43] , we tested if ADAMTS-5, that was also identified in our protease screen ( Table S1 ), could cleave Reelin. Although shRNA-mediated knock-down of ADAMTS-5 in HEK293 cells did not affect Reelin cleavage in the medium (data not shown), incubation of FL-Reelin with recombinant active ADAMTS-5 led to formation of Reelin proteolytic fragments, a process that could be fully inhibited by the addition of TIMP-3 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Atg4A or Atg4B were incubated with FRET-LC3B or FRET-GATE-16 at different concentrations in Buffer B in a total volume of 200 µl at 37°C for the designated times. The kinetics were determined as previously described 32 with modifications. In brief, the initial velocity of the cleavage reaction was defined as V = [S] t /t, in which [S] t is the substrate concentration ([S]) at a given time point (t).…”
Section: Methodsmentioning
confidence: 99%
“…Among them, ADAMTS‐5 (aggrecanase 2) appears to be a major aggrecanase in mice (6, 7), but both ADAMTS‐4 (aggrecanase 1) and ADAMTS‐5 are considered to play a role in human disease (8). Thus interest has been growing in the development of inhibitors for ADAMTS‐4 and ‐5 (911), mirroring the development of MMP inhibitors for the treatment of diseases associated with elevated MMP activity. Numerous MMP inhibitors have been developed, and several were clinically tested in patients with cancer (12) and rheumatoid arthritis (13), but they failed to show efficacy and exhibited side effects such as musculoskeletal pain and mild thrombocytopenia (12).…”
mentioning
confidence: 99%